Сканувальна мікроскопія - Баланюк, Юрій (Видавництво Національного університету «Львівська політехніка», 2009)
We traditionally use optical and television microscopes for study of biological microscopic object. Recently scanning optical microscopes have into production. These microscopes are equipped with a fine resolution electron-ray tube which functions as a lamp. The electron-ray tube glow is suggested at UV range. Owing to raster scanning principle of a biological microscopic object during microscope enlargement there is a possibility of selected biological microscopic object fragment absorbtion measuring. It will be also possible to measure optic density of selected fragment.To estimate incluced fluorescence the incluced radiation intensity at various specter sectors may be measured. Owing to raster scanning principle there is a possibility of image forming in the wider working field at deeper sharpness as compared to ordinary UV optical microscopic.
Keywords: optical and television microscopgenerator; electron-ray tube